Nanostructural Organization of Naturally Occurring Composites—Part II: Silica-Chitin-Based Biocomposites. (9th March 2008) - Ehrlich, Hermann; Janussen, Dorte; Simon, Paul; Bazhenov, Vasily V.; Shapkin, Nikolay P.; Erler, Christiane; Mertig, Michael; Born, René; Heinemann, Sascha; Hanke, Thomas; Worch, Hartmut; Vournakis, John N.
Abstract : Investigations of the micro- and nanostructures and chemical composition of the sponge skeletons as examples for natural structural biocomposites are of fundamental scientific relevance. Recently, we show that some demosponges ( Verongula gigantea, Aplysina sp.) and glass sponges ( Farrea occa, Euplectella aspergillum ) possess chitin as a component of their skeletons. The main practical approach we used for chitin isolation was based on alkali treatment of corresponding external layers of spicules sponge material with the aim of obtaining alkali-resistant compounds for detailed analysis. Here, we present a detailed study of the structural and physicochemical properties of spicules of the glass sponge Rossella fibulata . The structural similarity of chitin derived from this sponge to invertebrate alpha chitin has been confirmed by us unambiguously using physicochemical and biochemical methods. This is the first report of a silica-chitin composite biomaterial found in Rossella species . Finally, the present work includes a discussion related to strategies for the practical application of silica-chitin-based composites as biomaterials.